Citizenship education: A catalyst for national integration in Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
With Nigeria's long history, great natural and human resource endowment, and scientific and technological advancements, one would expect that a stable national integration of the country's society would have been created long ago. However, the current situation in Nigeria suggests that the journey thus far has left much to be desired, and national integration has become a non-issue in national debate. As a result of the country's current challenges, many people have called for secession, while others have advocated for restructuring, and true federalism can be traced back to the country's multicultural makeup. As a result, the goal of this essay is to look at the function of citizenship education in Nigeria's national integration process in order to come up with a solution to the country's current problems. Citizenship education has been defined as the development and production of active citizens who are socially responsible, socially sensitive, socially adaptable, and socially intelligent members of their immediate environment and larger society.
Keywords: Citizens; Nigeria; Society; Citizenship; National Integration